The Role of Bhabinkamtibmas in Resolving Domestic Violence in Rokan Hilir Area - Pramanto, Ariski; Hakim, Abdul; Jannah, Maya (International Journal Labs, 2024)
The problem of domestic violence or commonly abbreviated as domestic violence is sometimes not a problem for 2 people, both perpetrators and victims, but often this domestic violence can be a problem for the community to participate in solving it. One of the parties who usually participates in solving domestic violence cases is Bhabinkatibmas. In addition to Bhabinkamtibmas, the participating parties include the families of both perpetrators and victims, village heads, hamlet heads or neighborhood heads, community leaders and Bhabinkamtibmas itself. The police as one of the law enforcement officers responsible for law enforcement have the duty to carry out law enforcement, one of which is in acts of domestic violence and conduct investigations and provide protection for victims of domestic violence. The formulation of the problem in this study is: 1. What is the Role of Bhabinkamtibmas in Resolving Domestic Violence in the Rokan Hilir area? 2. What are the obstacles faced by Bhabinkamtibmas in tackling Domestic Violence in Rokan Hilir area? This study used Sociological juridical legal research. This sociological juridical legal research is conceptualized as the manifestation of symbolic meanings of social actors as seen in their interactions. That the real reality of life does not exist in the empirical realm which is also the realm of observation, does not appear in the form of objectively patterned and structured (let alone normative) behavior and can therefore be measured to produce quantitative data. The role of Bhabinkamtibmas in solving Domestic Violence includes: enforcing the law for the sake of creating security and order in the community itself. The resolution of acts of domestic violence committed by Bhabinkamtibmas in the Rokan Hilir Region encountered obstacles in the field, these obstacles include: Some victims of domestic violence are still reluctant to report their acts of violence, this causes Bhabinkamtibmas as a representative of law enforcement to be unable to do much or make enforcement efforts or conduct investigations because acts of domestic violence are complaint delicacy.